Surface modified ZnIn2S4 photocatalyst as well as preparation method and application thereof
By surface modification of ZnIn2S4, Vs-ZnIn2S4@Co composite material is formed, which solves the problem of easy recombination of photogenerated carriers of photocatalysts and low visible light utilization, significantly improves the photocatalytic hydrogen production efficiency, and achieves efficient clean energy Production.
Patent Information
- Application Number
- CN202411389263.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-03
AI Technical Summary
ZnIn2S4 photocatalysts have problems such as easy recombination of photogenerated carriers and low utilization of visible light, resulting in low photocatalytic hydrogen production efficiency.
By surface modification on ZnIn2S4, a mixed solvent of zinc source, indium source, thioacetamide and water and ethanol are used to undergo solvothermal reaction to form ZnIn2S4 with sulfur vacancy, and doped with the cobalt source solution under a protective atmosphere , fix Co atoms to form Vs-ZnIn2S4@Co composite material, and regulate the catalytic site and electron energy level structure.
The photocatalytic hydrogen production performance of ZnIn2S4 has been significantly improved, and the hydrogen production rate reaches 11 times that of unmodified ZnIn2S4, solving the problems of environmental pollution and energy shortage.
Smart Images

Figure CN119236972A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photocatalytic nano-semiconductor material synthesis, and in particular to a surface-modified ZnIn2S4 photocatalyst and a preparation method and application thereof. Background Art
[0002] In recent years, with the development of economy and the improvement of people's living standards, people need to exploit a large amount of fossil energy such as oil and natural gas, which are non-renewable energy sources and have very limited reserves on the earth. While exploiting and utilizing these fossil energy sources, gases such as carbon dioxide, carbon monoxide and other toxic and harmful substances will be emitted. Greenhouse gases such as carbon dioxide will aggravate global warming, and some toxic substances will even directly affect human life and health. In order to face the problems of environmental pollution and energy shortage, people urgently need to develop environmentally friendly, green and sustainable clean energy technologies to replace traditional fossil energy and reduce greenhouse gas emissions. Among many clean energy technologies, photocatalytic hydrogen production technology has attracted much attention. Photocatalytic hydrogen production technology can decompose water into hydrogen and oxygen, and use solar energy to convert water into hydrogen energy. In the process of hydrogen production, only water, semiconductor catalysts and solar energy are needed. It is a green, clean and efficient hydrogen production technology. Photocatalyst is the core of the photocatalytic hydrogen production system and determines the conversion rate of hydrogen energy in the whole reaction process. How to design and prepare a catalyst with high photocatalytic activity and stability to achieve efficient utilization of solar energy is a major problem in photocatalytic hydrogen production technology.
[0003] ZnIn2S4 has attracted much attention in the field of photocatalysis due to its excellent physical and chemical properties. It is a layered ternary sulfide semiconductor with an adjustable band gap width ranging from 2.06 to 2.85 eV, a visible light response region of up to 570 nm, and significant light absorption capacity. ZnIn2S4 is less toxic, has a simple preparation process, and is relatively abundant in sources. However, ZnIn2S4 still has disadvantages such as easy recombination of photogenerated carriers and low utilization of visible light, which seriously limits its practical application. Summary of the invention
[0004] The purpose of the present invention is to provide a surface-modified ZnIn2S4 photocatalyst and its preparation method and application, so as to solve the problems of ZnIn2S4 such as easy recombination of photogenerated carriers, low utilization rate of visible light and low efficiency of photocatalytic hydrogen production.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a surface-modified ZnIn2S4 photocatalyst, comprising the following steps:
[0007] (1) mixing a zinc source, an indium source, thioacetamide and a mixed solvent of water and ethanol to perform a solvothermal reaction to obtain ZnIn2S4 with sulfur vacancies;
[0008] (2) Under a protective atmosphere, ZnIn2S4 with sulfur vacancies, a cobalt source solution and water are mixed and doped to obtain a surface-modified ZnIn2S4 photocatalyst.
[0009] Preferably, in the preparation method, in step (1), the zinc source comprises one or more of zinc acetate, zinc chloride, zinc nitrate and zinc sulfate, the indium source comprises indium chloride and / or indium nitrate, and the molar ratio of the zinc source, the indium source and the thioacetamide is 1:1.8-2.2:11.8-12.2.
[0010] Preferably, in the preparation method, in step (1), the molar to volume ratio of the zinc source to the mixed solvent of water and ethanol is 0.3-0.5 mmol:50 mL; and in the mixed solvent of water and ethanol, the volume ratio of water to ethanol is 40-49:10-1.
[0011] Preferably, in the preparation method, in step (1), the temperature of the solvent thermal reaction is 200 to 220° C., and the time is 7 to 9 hours.
[0012] Preferably, in the preparation method, in step (2), the cobalt source solution comprises a cobalt chloride solution and / or a cobalt nitrate solution, and the concentration of the cobalt source solution is 3.8 to 4.2 mg / mL.
[0013] Preferably, in the preparation method, in step (2), the mass-to-volume ratio of the ZnIn2S4 having sulfur vacancies to the cobalt source solution is 0.2 g: 225-900 μL.
[0014] Preferably, in the preparation method, in step (2), the mass-to-volume ratio of the ZnIn2S4 having sulfur vacancies to the water is 0.18-0.2 g:150 mL.
[0015] Preferably, in the preparation method, in step (2), the doping temperature is 50 to 70° C. and the doping time is 6 to 8 hours.
[0016] The invention also provides a surface-modified ZnIn2S4 photocatalyst prepared by the preparation method.
[0017] The present invention also provides an application of the surface modified ZnIn2S4 photocatalyst in photocatalytic hydrogen production.
[0018] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:
[0019] (1) The present invention adopts a method of solvothermal reaction of zinc source, indium source, thioacetamide and a mixed solvent of water and ethanol. In the mixed solvent of water and ethanol, ethanol is used as a reducing agent, which will cause Zn on the surface of sulfur-indium-zinc 2+ andIn 3+ The coordination number is reduced, and part of the sulfur on the surface of sulfur indium zinc is reduced, resulting in the loss of sulfur atoms. ZnIn2S4 with sulfur vacancies is synthesized, and its morphology is novel; at the same time, the concentration of sulfur vacancies on the surface of ZnIn2S4 can be regulated by changing the volume ratio of water to ethanol. Sulfur vacancies on the surface of ZnIn2S4 can fix atomically dispersed Co, achieve precise doping of Co atoms, and form a surface-modified ZnIn2S4 photocatalyst (i.e., Vs-ZnIn2S4@Co composite material). Under the combined action of sulfur vacancies and Co doping, the complete separation of catalytic sites is achieved, which promotes the separation and transfer of photogenerated charges, effectively regulates its electronic energy level structure, and provides more reaction sites, thereby significantly improving the photocatalytic hydrogen production performance of ZnIn2S4. The hydrogen production rate is 11 times that of unmodified ZnIn2S4, which is of great significance for solving the problems of environmental pollution and energy shortage.
[0020] (2) The reaction raw materials of the present invention are easy to obtain, low in cost, and can be used in large-scale practical production. In addition, the preparation method of the present invention is simple and convenient, the reaction equipment is simple, the preparation cycle is short, and it is easy to operate. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for describing the embodiments or the prior art are briefly introduced below.
[0022] Figure 1 is the SEM image of the ZIS obtained in Experimental Example 1;
[0023] Figure 2 This is a SEM image of the Vs-ZIS obtained in step (1) of Example 1;
[0024] Figure 3 for Figure 2 The enlarged image of the area circled by the red dashed box;
[0025] Figure 4 Schematic diagram of the atomic arrangement surface of the ZIS obtained in Experimental Example 1 and the Vs-ZIS obtained in step (1) of Example 1;
[0026] Figure 5 This is the SEM image of Vs-ZIS@Co-3 obtained in Example 1;
[0027] Figure 6 XRD patterns of Vs-ZIS obtained in step (1) of Example 1 and Vs-ZIS@Co-3 obtained in Example 1;
[0028] Figure 7 This is the EPR spectrum of Vs-ZIS@Co-3 obtained in Example 1;
[0029] Figure 8 Schematic diagram of the atomic arrangement surface of Vs-ZIS@Co-3 obtained in Example 1;
[0030] Fig. 9 The photocatalytic hydrogen production results of the ZIS obtained in Experimental Example 1 and the Vs-ZIS obtained in step (1) of Example 1;
[0031] Fig.10 The photocatalytic hydrogen production results of the ZIS obtained in Experimental Example 1, the Vs-ZIS obtained in step (1) of Example 1, and the Vs-ZIS@Co-3 obtained in Example 1. DETAILED DESCRIPTION
[0032] The present invention provides a method for preparing a surface-modified ZnIn2S4 photocatalyst, comprising the following steps:
[0033] (1) mixing a zinc source, an indium source, thioacetamide and a mixed solvent of water and ethanol to perform a solvothermal reaction to obtain ZnIn2S4 with sulfur vacancies;
[0034] (2) Under a protective atmosphere, ZnIn2S4 with sulfur vacancies, a cobalt source solution and water are mixed and doped to obtain a surface-modified ZnIn2S4 photocatalyst.
[0035] In the present invention, the method of mixing the zinc source, the indium source, the thioacetamide and the mixed solvent of water and ethanol in step (1) is preferably as follows: the zinc source is first mixed with the mixed solvent of water and anhydrous ethanol; then the indium source is added thereto for second mixing; and then thioacetamide is added thereto for third mixing.
[0036] In the present invention, the first mixing time is preferably 3 to 5 minutes, more preferably 4 to 5 minutes, and more preferably 4 minutes.
[0037] In the present invention, the second mixing time is preferably 3 to 5 minutes, more preferably 4 to 5 minutes, and more preferably 4 minutes.
[0038] In the present invention, the third mixing time is preferably 30 to 50 min, more preferably 40 to 50 min, and more preferably 40 min.
[0039] In the present invention, the zinc source in step (1) preferably comprises one or more of zinc acetate, zinc chloride, zinc nitrate and zinc sulfate, further preferably comprises zinc acetate, zinc chloride, zinc nitrate or zinc sulfate, and more preferably is zinc acetate.
[0040] In the present invention, the indium source in step (1) preferably comprises indium chloride and / or indium nitrate, more preferably indium chloride or indium nitrate, and more preferably indium chloride.
[0041] In the present invention, the molar ratio of the zinc source, the indium source and the thioacetamide in step (1) is preferably 1:1.8-2.2:11.8-12.2, more preferably 1:1.9-2.1:11.9-12.1, and more preferably 1:2:12.
[0042] In the present invention, the molar to volume ratio of the zinc source to the mixed solvent of water and ethanol in step (1) is preferably 0.3-0.5 mmol:50 mL, more preferably 0.4-0.5 mmol:50 mL, and more preferably 0.5 mmol:50 mL.
[0043] In the present invention, in the mixed solvent of water and ethanol in step (1), the volume ratio of water to ethanol is preferably 40-49:10-1, more preferably 43-47:7-3, and more preferably 45:5.
[0044] In the present invention, the solvothermal reaction in step (1) is preferably carried out in a closed environment.
[0045] In the present invention, the temperature of the solvent thermal reaction in step (1) is preferably 200-220°C, more preferably 205-215°C, more preferably 210°C; the time is preferably 7-9h, more preferably 7-8h, more preferably 8h.
[0046] In the present invention, the solvothermal reaction in step (1) preferably further comprises: cooling, centrifugation, washing, and vacuum freeze-drying in sequence.
[0047] In the present invention, the cooling method is preferably: natural cooling to room temperature.
[0048] In the present invention, the centrifugal conditions are not limited, and any conditions well known to those skilled in the art may be used.
[0049] In the present invention, the washing method is preferably: washing with ethanol and water respectively.
[0050] In the present invention, the number of times of washing with ethanol and the number of times of washing with water are independently preferably 2 to 3 times, more preferably 2 times.
[0051] In the present invention, the vacuum freeze-drying time is preferably 10 to 14 hours, more preferably 12 to 14 hours, and more preferably 14 hours.
[0052] In the present invention, the method of mixing the ZnIn2S4 with sulfur vacancies, the cobalt source solution and water in step (2) is preferably: mixing the ZnIn2S4 with sulfur vacancies and water by ultrasonication, and then adding the cobalt source solution thereto and mixing and stirring.
[0053] In the present invention, the time of the mixed ultrasound is preferably 30 to 40 minutes, more preferably 30 to 35 minutes, and more preferably 35 minutes.
[0054] In the present invention, the mixing and stirring time is preferably 10 to 15 minutes, more preferably 12 to 15 minutes, and more preferably 15 minutes.
[0055] In the present invention, the cobalt source solution in step (2) preferably comprises a cobalt chloride solution and / or a cobalt nitrate solution, more preferably a cobalt chloride solution or a cobalt nitrate solution, and more preferably a cobalt chloride solution.
[0056] In the present invention, the concentration of the cobalt source solution in step (2) is preferably 3.8 to 4.2 mg / mL, more preferably 3.9 to 4.1 mg / mL, and even more preferably 4 mg / mL.
[0057] In the present invention, the mass-to-volume ratio of the ZnIn2S4 having sulfur vacancies to the cobalt source solution in step (2) is preferably 0.2 g: 225-900 μL, more preferably 0.2 g: 450-900 μL, and more preferably 0.2 g: 675 μL.
[0058] In the present invention, the mass-to-volume ratio of the ZnIn2S4 having sulfur vacancies to the water in step (2) is preferably 0.18-0.2 g:150 mL, more preferably 0.19-0.2 g:150 mL, and more preferably 0.2 g:150 mL.
[0059] In the present invention, the step (2) preferably further comprises: introducing a protective atmosphere into the reaction container before the doping.
[0060] In the present invention, the protective atmosphere is preferably nitrogen.
[0061] In the present invention, the time for introducing the protective atmosphere is preferably 30 to 40 minutes, more preferably 35 to 40 minutes, and more preferably 35 minutes.
[0062] In the present invention, the doping temperature in step (2) is preferably 50-70°C, more preferably 55-65°C, and more preferably 60°C; the doping time is preferably 6-8h, more preferably 6-7h, and more preferably 7h.
[0063] In the present invention, the doping in step (2) is preferably carried out by continuous dispersion.
[0064] In the present invention, the step (2) after the doping preferably further includes: cooling, centrifugation, washing, and vacuum freeze-drying in sequence.
[0065] In the present invention, the cooling method is preferably: natural cooling to room temperature.
[0066] In the present invention, the centrifugal conditions are not limited, and any conditions well known to those skilled in the art may be used.
[0067] In the present invention, the washing method is preferably: washing with water.
[0068] In the present invention, the number of times of washing with water is preferably 2 to 3 times, more preferably 2 times.
[0069] In the present invention, the vacuum freeze-drying time is preferably 10 to 14 hours, more preferably 12 to 14 hours, and more preferably 14 hours.
[0070] The invention also provides a surface-modified ZnIn2S4 photocatalyst prepared by the preparation method.
[0071] The present invention also provides an application of the surface modified ZnIn2S4 photocatalyst in photocatalytic hydrogen production.
[0072] In the present invention, the application method is not limited, and any method known to those skilled in the art may be used.
[0073] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0074] In the following specific examples, zinc acetate is Zn(Ac)2·2H2O, zinc sulfate is ZnSO4·7H2O, zinc chloride is ZnCl2, indium chloride is InCl3·4H2O, indium nitrate is In(NO3)3·4H2O, thioacetamide is TAA, water is deionized water, ethanol is anhydrous ethanol, cobalt chloride is CoCl2·6H2O, and cobalt nitrate is Co(NO3)2·6H2O.
[0075] Example 1
[0076] This embodiment provides a method for preparing a surface-modified ZnIn2S4 photocatalyst, comprising the following steps:
[0077] (1) Weigh 0.5 mmol Zn(Ac)2·2H2O and dissolve it in 50 mL of a mixed solvent of deionized water and anhydrous ethanol (volume ratio of deionized water to anhydrous ethanol = 45:5), and stir it magnetically for 5 min; weigh 1 mmol InCl3·4H2O and add it to the mixed solution, and stir it thoroughly for 5 min; weigh 6 mmol TAA and add it to the mixed solution, and stir it thoroughly for 30 min; transfer the stirred mixed solution into a 100 mL stainless steel reactor container lined with polytetrafluoroethylene, seal the reaction container, and heat it at 220°C for 9 h; the product is naturally cooled to room temperature, centrifuged to obtain a precipitate, and the precipitate is washed 3 times with ethanol and 3 times with deionized water, and then freeze-dried in vacuum for 12 h; a light yellow ZnIn2S4 with sulfur vacancies is obtained, which is denoted as Vs-ZIS, ZIS-5, Vs-ZnIn2S4 or ZnIn2S4-5;
[0078] (2) Weigh 0.2 g of ZnIn2S4 with sulfur vacancies and dissolve it in 150 mL of deionized water, and ultrasonically treat it for 30 min; weigh 675 μL of 4 mg / mL CoCl2·6H2O solution and add it to the above mixed solution, stir it thoroughly for 10 min; transfer the mixed solution to a three-necked flask, and continue to introduce nitrogen for 30 min; place the three-necked flask in a constant temperature heating magnetic stirrer, heat it at 70 °C for 8 h, and maintain a nitrogen atmosphere and continue stirring during the reaction; after the reaction, the product is naturally cooled to room temperature, the precipitate is centrifuged, and the precipitate is washed with deionized water 3 times, and then vacuum freeze-dried for 12 h to obtain a surface-modified ZnIn2S4 photocatalyst (i.e., Vs-ZnIn2S4@Co), which is recorded as Vs-ZIS@Co-3.
[0079] Experimental Example 1
[0080] This experimental example provides a method for preparing a ZnIn2S4 photocatalyst free of sulfur vacancies. The difference from Example 1 is that the mixed solvent of deionized water and anhydrous ethanol in step (1) of Example 1 is replaced with pure deionized water solvent to obtain ZnIn2S4 free of sulfur vacancies, denoted as ZIS; and step (2) is deleted.
[0081] Experimental Example 2
[0082] This experimental example provides a method for preparing ZnIn2S4 with sulfur vacancies. The difference from Example 1 is that the volume ratio of deionized water and anhydrous ethanol in step (1) of Example 1 is replaced with 49:1 to obtain ZnIn2S4 with sulfur vacancies, which is recorded as ZIS-1 or ZnIn2S4-1; and step (2) is deleted.
[0083] Experimental Example 3
[0084] This experimental example provides a method for preparing ZnIn2S4 with sulfur vacancies. The difference from Example 1 is that the volume ratio of deionized water and anhydrous ethanol in step (1) of Example 1 is replaced with 47:3 to obtain ZnIn2S4 with sulfur vacancies, which is recorded as ZIS-3 or ZnIn2S4-3; step (2) is deleted.
[0085] Experimental Example 4
[0086] This experimental example provides a method for preparing ZnIn2S4 with sulfur vacancies. The difference from Example 1 is that the volume ratio of deionized water and anhydrous ethanol in step (1) of Example 1 is replaced with 43:7 to obtain ZnIn2S4 with sulfur vacancies, which is recorded as ZIS-7 or ZnIn2S4-7; and step (2) is deleted.
[0087] Experimental Example 5
[0088] This experimental example provides a method for preparing ZnIn2S4 with sulfur vacancies. The difference from Example 1 is that the volume ratio of deionized water and anhydrous ethanol in step (1) of Example 1 is replaced with 40:10 to obtain ZnIn2S4 with sulfur vacancies, which is recorded as ZIS-10 or ZnIn2S4-10; and step (2) is deleted.
[0089] Observe the surface morphology of ZnIn2S4 obtained by different preparation methods. Figure 1 This is the SEM image of the ZIS obtained in Experimental Example 1. Figure 2 This is the SEM image of the Vs-ZIS obtained in step (1) of Example 1. Figure 3 for Figure 2 Enlarged image of the area circled by the red dashed box. Figures 1 to 3 The SEM results show that the morphology of ZIS and Vs-ZIS shows similarity, both showing a three-dimensional flower-like hierarchical structure formed by a combination of numerous interlaced nanosheets. The nanosheets in Vs-ZIS are thinner and larger, which indicates that the addition of ethanol inhibits the vertical growth of ZIS nanosheets and promotes the lateral growth of ZIS nanosheets. In addition, more obvious gaps can be observed in the flower-like microspheres of Vs-ZIS, which is conducive to contact with the reaction fluid and to improving the utilization of light through multiple reflections and scattering.
[0090] Figure 4 The schematic diagram of the atomic arrangement surface of the ZIS obtained in Experimental Example 1 and the Vs-ZIS obtained in step (1) of Example 1. The results show that a certain concentration of sulfur vacancies can be formed on the surface of the ZIS after being regulated by the mixed solvent of ethanol and water.
[0091] The sulfur vacancy concentration of ZnIn2S4 prepared by different methods was tested. The XPS fitting data of element peak area, S / In atomic ratio and Vs concentration in ZIS, ZIS-3 and Vs-ZIS are shown in Table 1, where the RSF (relative sensitivity factor) of Zn2p, In 3d and S2p are 28.72, 22.54 and 1.677, respectively.
[0092]
[0093] Area: the area corresponding to each element (RSF*T*MFP), the regulated ZIS: ZIS-3 and Vs-ZIS.
[0094] Table 1. XPS fitting data of ZIS, ZIS-3 and Vs-ZIS
[0095]
[0096] According to the data obtained by XPS, the Vs concentration is quantified based on the ratio of S atoms to In atoms. According to formulas 1 to 3, the atomic ratios of S:In of ZIS, ZIS-3 and Vs-ZIS samples are 2.04, 2.00 and 1.93, respectively. The Vs concentrations of the corresponding samples are calculated by normalization to be 0%, 1.96% and 5.39%.
[0097] Figure 5 This is a SEM image of Vs-ZIS@Co-3 obtained in Example 1. The results show that the macroscopic morphology of Vs-ZIS@Co-3 also shows a three-dimensional nanoflower ball assembled from many cross-linked nanosheets. This unique three-dimensional layered structure can promote the collection of light and achieve multiple light reflections. Compared with Vs-ZIS, the morphology of Vs-ZIS@Co-3 has not changed significantly, indicating that Co doping has almost no effect on the morphology of Vs-ZIS.
[0098] Figure 6 The XRD patterns of Vs-ZIS obtained in step (1) of Example 1 and Vs-ZIS@Co-3 obtained in Example 1 are shown. The results show that both catalysts point to the hexagonal ZnIn2S4 phase (JCPDS No.65-2023), and the characteristic peaks are located near 21.59°, 27°, 69°, 30.45°, 39.77°, 47.18°, 52.44°, 55.58° and 75.82°, corresponding to {006}, {102}, {104}, {108}, {102}, {110}, {116}, {022} and {212} crystal planes, respectively. After the introduction of Co, no diffraction peaks of Vs-ZIS@Co-3 were detected in the sample, indicating that the addition of Co cannot change the crystal structure of Vs-ZIS.
[0099] Figure 7 This is the EPR spectrum of Vs-ZIS@Co-3 obtained in Example 1. The results show that the signal at g = 2.003 is a sulfur vacancy signal, indicating that there are sulfur vacancies (Vs) in Vs-ZIS and Vs-ZIS@Co-3, and the signal of Vs-ZIS@Co-3 at g = 2.003 is weaker than that of Vs-ZIS, indicating that the S vacancy concentration of Vs-ZIS@Co-3 photocatalyst decreases after the introduction of Co, indicating that Co fills the S vacancies under its induced effect.
[0100] Figure 8 The schematic diagram of the atomic arrangement surface of Vs-ZIS@Co-3 obtained in Example 1. Figure 4 The results show that a large amount of Vs is generated on the surface of Vs-ZIS, which provides suitable sites for the anchoring of Co atoms.
[0101] Test Example 1
[0102] The test was carried out in a 150mL Labsolar-Ⅲ (AG) (Perfil, China) all-quartz glass automatic online trace gas analysis system with an exposed and sealed top. A 300W xenon lamp (PLS-SXE300) equipped with an ultraviolet cutoff filter (λ>420nm) was used as the light source and was placed 10cm above the reactor. The specific operation process is as follows: 5mg of ZIS obtained in Experimental Example 1, Vs-ZIS obtained in step (1) of Example 1, and Vs-ZIS@Co-3 obtained in Example 1 were weighed and added to 100mL of aqueous solution (containing 0.2M ascorbic acid as a sacrificial agent), and ultrasonicated for 1min to fully disperse the catalyst. Before the hydrogen evolution experiment was carried out, argon was purged for 30min to remove the air in the reactor. During the reaction, it was necessary to stir continuously to keep the solution uniform, and the reactor was kept at 10℃ using circulating cooling water. Finally, the amount of gas produced from the sealed quartz reactor every half an hour was measured by gas chromatograph (FLGC 9790Ⅱ, TCD) to evaluate the hydrogen production performance.
[0103] The results of test case 1 are as follows Fig. 9 , Fig.10 shown. Fig. 9 The results showed that the photocatalytic hydrogen production rate of ZIS under visible light was 1.02 mmol·g -1 ·h -1. After vacancy engineering regulated ZIS nanosheets, Vs-ZIS showed obvious photocatalytic activity for hydrogen production from water decomposition. This may be due to the large band gap of ZIS, which cannot fully utilize visible light and has a low separation efficiency of photogenerated electrons and holes. The Vs concentration on the surface of ZIS nanosheets was regulated by changing the volume ratio of deionized water / ethanol. When the volume ratio of deionized water / ethanol was 45:5, the photocatalytic hydrogen production rate of the Vs-ZIS catalyst was 5.13 mmol·g -1 ·h -1 , the hydrogen production rate is 5 times that of the original ZIS. Fig.10 The results show that the photocatalytic hydrogen evolution performance of Vs-ZIS@Co-3 is 11.36mmol·g -1 ·h -1 , about Vs-ZIS (5.13mmol·g -1 ·h -1 ) is twice that of ZIS (1.02mmol·g -1 ·h -1 )11 times.
[0104] Example 2
[0105] This embodiment provides a method for preparing a surface-modified ZnIn2S4 photocatalyst. The difference from Embodiment 1 is that the volume of the CoCl2·6H2O solution in step (2) is replaced with 225 μL, and the other parameter conditions are the same as those in Embodiment 1, denoted as Vs-ZIS@Co-1.
[0106] Example 3
[0107] This embodiment provides a method for preparing a surface-modified ZnIn2S4 photocatalyst. The difference from Embodiment 1 is that the volume of the CoCl2·6H2O solution in step (2) is replaced with 450 μL, and the other parameter conditions are the same as those in Embodiment 1, which is recorded as Vs-ZIS@Co-2.
[0108] Example 4
[0109] This embodiment provides a method for preparing a surface-modified ZnIn2S4 photocatalyst. The difference from Embodiment 1 is that the volume of the CoCl2·6H2O solution in step (2) is replaced with 900 μL, and the other parameter conditions are the same as those in Embodiment 1, which is recorded as Vs-ZIS@Co-4.
[0110] The sulfur vacancy concentration of the surface modified ZnIn2S4 photocatalyst obtained with different Co doping amounts was tested. The XPS fitting data of the element peak area, Co atomic concentration, S / In atomic ratio and Vs concentration in Vs-ZIS and Vs-ZIS@Co-y (y=1-4) are shown in Table 2 and Table 2, where the RSFs (relative sensitivity factors) of Zn2p, In 3d, S2p and Co 2p are 28.72, 22.54, 1.677 and 19.16, respectively.
[0111] Table 2. XPS fitting data of Vs-ZIS and Vs-ZIS@Co-y (y=1-4)
[0112]
[0113] Table 2. XPS fitting data of Vs-ZIS and Vs-ZIS@Co-y (y=1-4)
[0114]
[0115] The results in Table 2 and Table 2 show that the Vs concentration can be quantified by comparing S atoms and In atoms when the In atomic content in all samples is normal. The S / In atomic ratios of Vs-ZIS and Vs-ZIS@Co-y (y=1-4) samples are calculated to be 1.93, 1.93, 1.96, 2.00, and 2.01, respectively. The Vs concentrations of the corresponding samples are 5.39%, 5.39%, 3.92%, 1.96%, and 1.47%, respectively. The S vacancy concentration of Vs-ZIS@Co-3 photocatalyst decreases after the introduction of Co, indicating that Co fills S vacancies under its induced effect.
[0116] Example 5
[0117] The present embodiment provides a method for preparing a surface-modified ZnIn2S4 photocatalyst. The difference from Embodiment 1 is that the raw material in step (1) is replaced by ZnSO4·7H2O, the raw material is replaced by In(NO3)3·4H2O, the reaction conditions in step (1) are modified to heating at 200°C for 7 h, the reaction conditions in step (2) are modified to heating at 60°C for 7 h, the vacuum freeze-drying time in step (1) and step (2) is modified to 14 h, and the other parameter conditions are the same as those in Embodiment 1.
[0118] Example 6
[0119] The present embodiment provides a method for preparing a surface-modified ZnIn2S4 photocatalyst. The difference from Embodiment 1 is that the raw material in step (1) is replaced by ZnCl2, the reaction conditions in step (1) are modified to heating at 210°C for 8 h, the raw material in step (2) is replaced by Co(NO3)2·6H2O solution, the reaction conditions in step (2) are modified to heating at 50°C for 6 h, the vacuum freeze-drying time in step (1) and step (2) is modified to 10 h, and the other parameter conditions are the same as those in Embodiment 1.
[0120] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a surface-modified ZnIn2S4 photocatalyst, characterized in that: The following steps are involved: (1) mixing a zinc source, an indium source, thioacetamide and a mixed solvent of water and ethanol to perform a solvothermal reaction to obtain ZnIn2S4 with sulfur vacancies; (2) Under a protective atmosphere, ZnIn2S4 with sulfur vacancies, a cobalt source solution and water are mixed and doped to obtain a surface-modified ZnIn2S4 photocatalyst.
2. The preparation method according to claim 1, characterized in that: In step (1), the zinc source comprises one or more of zinc acetate, zinc chloride, zinc nitrate and zinc sulfate, the indium source comprises indium chloride and / or indium nitrate, and the molar ratio of the zinc source, the indium source and the thioacetamide is 1:1.8-2.2:11.8-12.
2.
3. The preparation method according to claim 1 or 2, characterized in that: In step (1), the molar to volume ratio of the zinc source to the mixed solvent of water and ethanol is 0.3-0.5 mmol:50 mL; in the mixed solvent of water and ethanol, the volume ratio of water to ethanol is 40-49:10-1.
4. The preparation method according to claim 3, characterized in that: In step (1), the temperature of the solvent thermal reaction is 200-220° C. and the time is 7-9 hours.
5. The preparation method according to claim 1, characterized in that: In step (2), the cobalt source solution comprises a cobalt chloride solution and / or a cobalt nitrate solution, and the concentration of the cobalt source solution is 3.8 to 4.2 mg / mL.
6. The preparation method according to claim 1 or 5, characterized in that: In step (2), the mass-to-volume ratio of the ZnIn2S4 having sulfur vacancies to the cobalt source solution is 0.2 g: 225-900 μL.
7. The preparation method according to claim 6, characterized in that: In step (2), the mass-to-volume ratio of the ZnIn2S4 having sulfur vacancies to the water is 0.18-0.2 g:150 mL.
8. The preparation method according to claim 7, characterized in that: In step (2), the doping temperature is 50-70° C. and the doping time is 6-8 hours.
9. The surface-modified ZnIn2S4 photocatalyst prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the surface modified ZnIn2S4 photocatalyst according to claim 9 in photocatalytic hydrogen production.